How COVID-19 Pandemic Affected the Treatment and Rehabilitation of Distal Radius Fracture? Data from a Peripheral General Hospital in Crete - Anna, Pantouvaki; Grigorios, Kastanis (International Journal of Innovative Research in Medical Science, 2021)
Objectives: The purpose of this study is to evaluate the frequency of unstable distal radius fractures in adult population and the management performed in orthopaedic and physiotherapy department of the General Hospital” Venizeleio” in Heraklion-Crete re-organised due to pandemic period. In pandemic period, due to urgent needs of covid-19 patients, a lot of orthopaedic associations suggested some restrictions concerning the treatment of DRF. The aim of this study is to answer in two hypothetical questions. First, did patients with unstable DRF receive a conservative instead of surgical treatment and second is the protocol of rehabilitation program still the same or do the patients receive a modified rehabilitation program? Methods: Patients admitted in the emergency department of the hospital during pandemic period of 2020 with distal radius fracture surgically treated, were evaluated and data compared with those of pre-pandemic period. (2018-2019). Results: A number of 32, 35 and 42 patients with DRF were treated and hospitalized in 2018, 2019 (pre-pandemic period) and 2020 (pandemic period) respectively. The mean age of patients did not appear with any statistical difference. (p= .93) between periods and causes of DRF did not change dramatically. Additionally, there was a remarkable variation in number of patients between the 1st and 2nd semesters of quarantine period. (p=.68). Conclusion: Adaptations in management of distal radius fracture during lockdown did not affect patient’s surgical and rehabilitation treatment and functional outcomes. The mean age of patients treated, did not vary during pandemic period while the causes of DRF. But it was obligatory to adopt the rehabilitation treatment plan and the number of hospital visits due to Covid-19 precautions.